The Analysis of Code Mixing Used by Livy Renata in Tema Indonesia Youtube Channel - Asmoro, Muhammad Panji; Annaningtyas, Cucut (Politeknik Harapan Bangsa Surakarta, 2023)
Nowadays, people using not only one language but more than one languages. Especially in Indonesian people using bilingualism language and also multilingualism. Indonesian people using these bilingual language for daily conversation. This is happened because Indonesia is a country that has many tribes and each tribe has a different regional language. The impact of this bilingualism language is people used code mixing in the conversation. Livy Renata is one of the guest in Tema Indonesia YouTube Channel who always using code mixing. Thus, it is significant to investigate the use of code mixing in this Tema Indonesia YouTube Channel. The aim of this study is to find out the types of code mixing that are used in Tema Indonesia YouTube Channel and also to figure out the type of code mixing that is most frequently used in this Channel. This research is used qualitative method. This study employed content analysis which focused on analyzing the types of code mixing which defined by the levels of code mixing that argued by Suwito. Then, The result after analyzing the video, there were 20 data in the levels of code mixing. In the levels of code mixing, the dominant level was word level and the lowest level was phrase level.